Effectiveness of Natural Farming Inputs on Agronomic Performance of French Bean (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
The use of natural farming inputs is considered a viable alternative to synthetic and inorganic chemicals in agriculture, aligning with the principles of organic cultivation and sustainability. The present study was undertaken to evaluate the effect of natural farming inputs on the growth of French bean (Phaseolus vulgaris L.). The field experiment was conducted during 2024 at Department of Horticulture, School of Agriculture, ITM University, Gwalior. The experiment consisted of nine treatments in randomized block design with three replications. The treatments were used T1- Control, T2- RDF (60:120:50 kg ha-1), T3- Vermicompost + 70% R.D.F., T4- Beejamrit (1 litre/kg seed) + Jeevamrit (100 %) at weekly interval, T5- Beejamrit (1 litre/kg seed) + Ghanjeevamrit (100 %), T6- Beejamrit (1 litre/kg seed) + Jeevamrit (75 %) + Ghanjeevamrit (25 %), T7- Beejamrit (1 litre/kg seed) + Jeevamrit (50 %) + Ghanjeevamrit (50 %), T8- Beejamrit (1 litre/kg seed) + Jeevamrit (25 %) + Ghanjeevamrit (75 %) and T9- Beejamrit (1 litre/kg seed) + Jeevamrit (80 %)+ Ghanjeevamrit (80%). Treatment no. 7 i.e. Beejamrit (1 litre/kg seed) + Jeevamrit (50 %) + Ghanjeevamrit (50 %) showed fastest 50 % germination and 50 % flowering days. Beejamrit (1 litre/kg seed) + Jeevamrit (50 %) + Ghanjeevamrit (50 %) stands out with the highest mean among all treatments for leaf area and number of pods per plant.
Keywords: Natural farming; jeevamrit; beejamrit and growth